Physical chemistry insights into surface charge phenomena during frictional coupling in triboelectric X-ray sources. Issue 25 (5th June 2019) - Pezzotti, Giuseppe; Camara, Carlos; Marin, Elia; Zhu, Wenliang; Green, Douglas; Collins, Adam; Putterman, Seth
Abstract : This study delves into molecular-scale phenomena that govern the frictional coupling of triboelectric materials used in miniaturized X-ray sources. Abstract : This study delves into molecular-scale phenomena that govern the frictional coupling of triboelectric materials used in miniaturized X-ray sources. A frictional couple consisting of diamond-like carbon (DLC) and polymeric Kapton gained attention. To gain insights into the microscopic nature of this process, we performed a series of spectroscopic experiments using Raman spectroscopy and X-ray photoelectron spectroscopy (XPS) on both unused and used components. This set of spectroscopic characterizations provided relevant notions on how contact electrification accompanies changes in materials' composition near the surface. As a general trend, contact electrification at increasing frictional loads gave rise to clear changes in the DLC Raman emissions. The emission assigned to sp 2 CC stretching in the amorphous structure ( i.e., the so-called D-band) increased in relative intensity vs. the homologous vibration in the graphitic structure (the G-band). On the polymeric side, increases in friction involved the progressive annihilation of carboxylic rings, as revealed by reduction in the relative intensity of the Raman band representative of ring vibrations in carboxylic acid with respect to the band associated with the vibrations of the imide ring. With experiments being conducted under vacuum, our findings suggested that contact charging involves heterolytic bond breaking and that the emergence of electrification is the final output of bond cleavage and chemical changes at the molecular scale. There were exceptions to the general trend described above, which prompted the possibility of engineering the materials' surface at the molecular scale to maximize the macroscopically observed charging and X-ray emission trends.